Корифей української культури ХХ століття (До 110-річчя від дня народження Максима Рильського) - Фільц, Б. (Народна творчість та етнографія, 2005)
This article is dedicated to the wide range of M. Rylsky's activities as a publisher, poet, musicologist, literary critic, publicist. Special attention the author of the article is given to the connections between Rylsky's poetry and Ukrainian music written for this poetry. Ya. Stepovy was the first composer who turned his attention to Rylsky's poetry. Then - L. Revutsky ("The monologue of Taras Bul'ba"). Author is mentioning also that M. Rylsky was a founder of the anthology of the folklore of different genres when he was a director of the Institute Art Studies, Folklore and Ethnography.